In Vivo Imaging Sheds Light on Immune Cell Migration and Function in Cancer - Torcellan, Tommaso; Stolp, Jessica; Chtanova, Tatyana (Frontiers in Immunology, 2017)
There is ample evidence for both beneficial and harmful involvement of the immune system in tumor development and spread. Immune cell recruitment to tumors is essential not only for the success of anti-cancer immune therapies but also for tumor-induced immune suppression. Now that immune-based therapies are playing an increasingly important role in treatment of solid tumors such as metastatic melanomas, precise analysis of the in vivo contributions of different leukocyte subsets in tumor immunity has become an even greater priority. Recently this goal has been markedly facilitated by the use of intravital microscopy, which has enabled us to visualize the dynamic interactions between cells of the immune system and tumor targets in the context of the tumor microenvironment. For example, intravital imaging techniques have shed new light on T cell infiltration of tumors, the mechanisms of cancer cell killing and how myeloid cells contribute to tumor tolerance and spread. This mini-review summarizes the recent advances made to our understanding of the roles of innate and adaptive immune cells in cancer based on the use of these in vivo imaging approaches.